Low luminance visual acuity as a clinical measure and clinical trial outcome measure: a scoping review - Wood, LJ; Jolly, JK; Buckley, TM; Josan, AS; MacLaren, RE (Wiley, 2021)
Purpose: The measurement of standard visual acuity (VA) is the most well‐known part of any ophthalmic examination to indicate visual function. Despite this, it is insensitive in detecting early disease changes. Therefore, other visual function tests have been developed including low luminance VA (LLVA) and low luminance deficit (LLD). This scoping literature review aims to summarise the current published applications of LLVA and LLD assessments to evaluate their utility as clinical markers and research outcome measures in a variety of ophthalmic conditions.